Validity and reliability of a thoracic kyphotic assessment tool measuring distance of the seventh cervical vertebra from the wall - Pipatana Amatachaya, PhD; Sawitree Wongsa, MSc; Thanat Sooknuan, M. Eng; Thiwabhorn Thaweewannakij, PhD; Maneepan Laophosri, MSc; Nuttaset Manimanakorn, MD, PhD; Sugalya Amatachaya, PhD (World Scientific Publishing, 2016)
Background: In primary healthcare (PHC) service, community residents, village health volunteers (VHVs), and healthcare professionals need to work in partnership to facilitate universal and equitable healthcare services. However, these partnerships may need an appropriate tool helping them to execute an effective health-related activity. Objectives: To investigate the reliability and validity of a simple kyphosis measure using a perpendicular distance from the seventh cervical vertebra (C7) to the wall (C7WD). Methods: Elderly people with different degrees of kyphosis (n = 179) were cross-sectionally investigated for the intra- and interrater reliability of the measurement by a physical therapist (PT), VHV, and caregiver. The validity was assessed in terms of concurrent validity as compared with the Flexicurve, and discriminative validity for functional deterioration in participants with mild, moderate, and severe kyphosis. Results: The method showed excellent reliability among PT, VHV, and caregivers (ICC > 0.90, p < 0.001), and excellent correlation to the data from the Flexicurve. Results of the assessment were greater than a level of minimal detectable change and could clearly discriminate functional deterioration in participants with different severity of kyphosis (p < 0.001). Conclusion: C7WD is valid and reliable, thus it can be used to promote the standardisation of kyphosis measures among PHC members.